Clinico hematological profile of pancytopenia in pediatric patients: an institutional experience in North Himalayan region of India - Rawat, Anil; Mamgain, Varun; Chandra, Smita; Kalra, B. P. (International Journal of Research in Medical Sciences, 2020)
Background: Pancytopenia is a common clinical pattern with an extensive differential diagnosis, but literature search shows only limited studies of pancytopenia in Pediatrics patients in Uttarakhand state of India. The present study was therefore conducted to study the spectrum of pancytopenia with bone marrow and haematological profile in Pediatrics patients in this north Himalayan state of India. Methods: Prospective observational study was conducted in the Department of Pediatrics in the teaching institute situated in Uttarakhand state of India over a period of 12 months. The study included all the patients of pancytopenia below 18 years of age who underwent bone marrow examination after written informed consent. Results: The study included total 50 pediatrics patients of pancytopenia with male to female ratio of 1.38:1. The mean age of patients was 10.58±4.94 with median age of 12 years. Mean hemoglobin was 5.31±2.09 g/dl, total leukocyte count was 2492.68±941.76/mm3, platelet count was 34724±26423/mm3, mean corpuscular volume was 90.95±16.65 fl, mean corpuscular hemoglobin was 30.11±6.07 pg, mean corpuscular hemoglobin concentration was 33.06±1.65% and reticulocyte count was 1.21±1.10%. Nutritional deficiency (28%) was the most common cause for pancytopenia followed by aplastic anemia (24%). Megaloblastic anemia was the commonest cause of nutritional deficiency anemia (71.42%) with pancytopenia. Conclusions: Pancytopenia is an important presentation in Pediatrics population with the most common cause being nutritional anemia and aplastic anemia. Megaloblastic anemia is the commonest cause of nutritional anemia with pancytopenia. The clinicians should be aware of spectrum of pancytopenia with clinical and haematological presentation in Pediatrics patients of this region so as to avoid unnecessary work ups and delay in treatment.